PET imaging of 18F-florbetapir in cognitively impaired individuals: Lack of activity within the cerebellar cortex - Michael A. Meyer; Allison Caccia; Danielle Martinez; Mark A. Mingos (MDPI AG, 2018)
Ten individuals suspected of having possible Alzheimer disease underwent PET imaging using 18F-Flubetapir. Only one of ten individuals had a pattern typical for normal elderly control subjects with 9 of the 10 showing a Alzheimer type pattern for the cerebral cortex yet all 10 subjects had uniformly low to absent tracer localization to the cerebellar cortex; significantly high tracer activity was noted within the subcortical white matter of the cerebellum in a symmetric manner in all cases. In consideration of studies that have shown amyloid deposits within the cerebellar cortex in 90% of pathologically proven cases of Alzheimer's disease, these findings raise questions about the actual clinical value of florbetapir PET imaging in evaluating cerebellar involvement and raises questions whether PET imaging of this tracer accurately portrays patterns of amyloid deposition, as there is rapid hepatic metabolism of the parent compound after intravenous injection. Possible links to Alzheimer's disease related alterations in blood-brain barrier permeability to the parent compound and subsequent radiolabelled metabolites are discussed as potential mechanisms that could explain the associated localization of the tracer to the brainstem and subcortical white matter within the cerebrum and cerebellum of Alzheimer's disease patients.